Dramaturgy in Identity Formation on Social Media: A Study on Second Account Ownership on Instagram - Musfiah Saidah; Hilda Trianutami (Universitas Multimedia Nusantara, 2022)
The second Instagram account is a privacy management effort that is often abused. The main purpose of limiting privacy actually ends up being excessive uploading of information. The demands for the existence of identity spur social media users to publish on a large scale. The theory used in this research is dramaturgy combined with the concept of identity and self-disclosure. In Dramaturgy the roles that are displayed on each stage can be different according to the needs. This research uses a qualitative approach with a case study method. The data is deepened through interviews and literature sources from books, journals and articles. As a result, it was found that most of the second account owners used the account as a venue for self-expression. However, unfortunately many of these behaviors are carried out without considering the threatening side effects.